2014
DOI: 10.4330/wjc.v6.i5.327
|View full text |Cite
|
Sign up to set email alerts
|

Elevated blood pressure: Our family’s fault? The genetics of essential hypertension

Abstract: Genetic hypertension risk algorithms could be developed in the future but may be of limited benefit due to the multi-factorial nature of EH. With emerging technologies, like next-generation sequencing, more direct causal relationships between genetic and epigenetic factors affecting EH will likely be discovered creating a tremendous potential for personalized medicine using pharmacogenomics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 0 publications
0
20
0
2
Order By: Relevance
“…However, not all persons with risk alleles exposed to inciting events develop issues. It seems likely that environmental events can impact the epigenome, giving rise to later disease, and also increasing the chance that medical problems may develop [74][75][76]. Epigenetic changes involve methylation and hydroxymethylation of DNA bases, histone modification, as well as RNA modifications (via short RNAs and long noncoding RNAs) within the nucleus [75].…”
Section: Genetics and Epigenetics And Blood Pressurementioning
confidence: 98%
See 1 more Smart Citation
“…However, not all persons with risk alleles exposed to inciting events develop issues. It seems likely that environmental events can impact the epigenome, giving rise to later disease, and also increasing the chance that medical problems may develop [74][75][76]. Epigenetic changes involve methylation and hydroxymethylation of DNA bases, histone modification, as well as RNA modifications (via short RNAs and long noncoding RNAs) within the nucleus [75].…”
Section: Genetics and Epigenetics And Blood Pressurementioning
confidence: 98%
“…A number of genomewide association studies have focused on epigenetic changes [74]. Interestingly, associations include genes already linked to hypertension, such as WNK4 (decreased transcription and increased histone acetylation), NKCC1 (methylation in the promotor regulation or hypomethylation in the promotor region) and ENaCa (methylation of Lys79 of histone H3).…”
Section: Genetics and Epigenetics And Blood Pressurementioning
confidence: 99%
“…With advances in genomic, epigenomic, transcriptomic, and proteomic research technologies, it is now possible to find novel rare genetic variants with significant effects on EH. These can be captured by larger genome-wide association studies combined with sequencing large targeted stretches of DNA, whole exome, or genome using next-generation sequencing techniques [9, 10]. In addition, research advances in epigenetic/epigenomic modification play a partial role in genetic hypertension; these include DNA methylation analysis at the genome level using microarray hybridization or next-generation sequencing, posttranslational modification of histone analyzing by the proteomic technique, and regulatory non-coding RNA analysis through the transcriptomic technique [11-13].…”
Section: Essential Hypertension (Eh)mentioning
confidence: 99%
“…1 Epidemiological studies and clinical trials implied that EH is mainly caused by genetic factors. Family-based studies have shown that the genetic contribution to the variation of individual blood pressure (BP) reached 23% 2 and up to 60% in twin research.…”
Section: Introductionmentioning
confidence: 99%